A Clinical Study Of Maternal And Fetal Outcome In Cases Of Abruptio Placentae - Shah, Stuti; Macwan, Priyal; Dhanger, Anamika; Patel, Aayush; Kagathara, Manali (Journal of Neonatal Surgery, 2025)
Background Placental abruption (abruptio placentae) is a life-threatening obstetric emergency contributing substantially to global maternal morbidity/mortality and perinatal loss. The burden in low- and middle-income settings remains under-reported. Methods We performed a prospective observational study in the Department of Obstetrics and Gynaecology, GMERS Medical College, Gandhinagar (November 2022 – April 2024). All singleton pregnancies ≥ 28 weeks with clinically or ultrasonographically confirmed abruption were enrolled (n = 109). Maternal socio-demographic details, etiological factors, Page’s grade, interventions, and fetomaternal outcomes were recorded. Data were analysed with Epi-Info 7; results are expressed as mean ± SD, proportions, and case-fatality rate. Results Incidence was 1.26 % (109/8 613 deliveries). Mean maternal age was 27.1 ± 4.5 years; 86 % resided in rural areas and 80 % were unbooked. Grade 2 abruption predominated (51.4 %). Pre-eclampsia spectrum (40.2 %), anaemia (70.6 %), and multiparity were major risk factors. Vaginal delivery occurred in 54 %, caesarean section in 46 %. Maternal complications included postpartum haemorrhage (26.6 %), shock (11 %), acute renal failure (9.2 %) and DIC (3.7 %). Maternal case-fatality rate was 1.96 %. Mean birth-weight was 1.87 ± 0.62 kg; 65 % of neonates had 1-min Apgar < 7 and 43 % required NICU admission. Overall intra-uterine death plus stillbirth rate was 43.2 %, and perinatal mortality 19.3 %. Conclusion Abruptio placentae remains a formidable contributor to adverse fetomaternal outcomes. Early detection of hypertensive disorders, timely referral, and preparedness for massive transfusion can mitigate morbidity. Strengthening antenatal coverage in rural populations is paramount.